2017
DOI: 10.1103/physreve.96.042405
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of cationic antimicrobial peptides and divalent cations on bacterial lipopolysaccharides

Abstract: The permeability of the bacterial outer membrane, enclosing Gram-negative bacteria, depends on the interactions of the outer, lipopolysaccharide (LPS) layer, with surrounding ions and molecules. We present a coarse-grained model for describing how cationic amphiphilic molecules (e.g., antimicrobial peptides) interact with and perturb the LPS layer in a biologically relevant medium, containing monovalent and divalent salt ions (e.g., Mg 2+ ). In our approach, peptide binding is driven by electrostatic and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 54 publications
3
70
0
Order By: Relevance
“…It is worth noting that antimicrobial peptide TS can neutralize LPSs to move through the OM LPS barrier to the bacterial intima and then destroy the intima to kill the bacteria. In addition, several scientists have found that the positively charged biological amino acids of AMPs bind to negatively charged LPSs on the OM of gram-negative bacteria through Mg 2+ and Ca 2+ ion competition [34,35]. The same result can be observed in this experiment ( Figure 5D).…”
Section: Interaction Of Peptides With Lipopolysaccharidessupporting
confidence: 84%
See 1 more Smart Citation
“…It is worth noting that antimicrobial peptide TS can neutralize LPSs to move through the OM LPS barrier to the bacterial intima and then destroy the intima to kill the bacteria. In addition, several scientists have found that the positively charged biological amino acids of AMPs bind to negatively charged LPSs on the OM of gram-negative bacteria through Mg 2+ and Ca 2+ ion competition [34,35]. The same result can be observed in this experiment ( Figure 5D).…”
Section: Interaction Of Peptides With Lipopolysaccharidessupporting
confidence: 84%
“…Lipopolysaccharides, a major constituent of OM of gram-negative bacteria, are considered to be the first permeability barrier that blocks the entry of harmful reagents including antibiotics and host proteins [30,31]. Majority cationic antibacterial peptides can bind to negatively charged LPSs on the OM of gramnegative bacteria [32][33][34]. It is worth noting that antimicrobial peptide TS can neutralize LPSs to move through the OM LPS barrier to the bacterial intima and then destroy the intima to kill the bacteria.…”
Section: Interaction Of Peptides With Lipopolysaccharidesmentioning
confidence: 99%
“…With increasing computer power, lower resolution (coarse grain), and better algorithms for exploiting today's computer architectures, they also reveal how molecules interact and how supramolecular complexes form and evolve. MD simulations have been used, for example, to follow the insertion of hydrophobic peptides into the membrane, where they assemble into transmembrane helical bundles (Tieleman et al 2002) and how magainin interacts with lipopolysaccharides (Smart et al 2017). Furthermore, they permitted the visualization of the deformation of the lipid bilayer in the presence of in-plane oriented amphipathic peptides.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…All-atom 100 ns simulations in palmitoyl-oleoyl-phosphatidylethanolamine/ palmitoyl-oleoyl-phosphatidylglycerol (POPE/POPG) 3/1 of one, two, or eight peptides and 512 lipids show a stable in-plane topology of magainin and pleurocidin, some oligomerization, but no pore or supramolecular rearrangement within this time frame [ 110 ]. Finally, recent simulation work investigating magainin 2-lipopolysaccharide and ion interactions shall be mentioned [ 111 ].…”
Section: Introductionmentioning
confidence: 99%